2009
DOI: 10.5575/geosoc.115.266
|View full text |Cite
|
Sign up to set email alerts
|

Genesis and evolutional processes of the Paleozoic oceanic island arc crust, Asago body of the Yakuno Ophiolite, Southwest Japan

Abstract: A middle to lower crustal section of Paleozoic oceanic island arc is exposed in the Asago body of the Yakuno ophiolite. Based on field occurrence, petrography, and geochemical modeling, we investigated the evolution of the Asago body and relevant magmatic processes. The Asago body consists of two stages of rocks. The first-stage rocks consist of metagabbro and schistose amphibolite that represent the basement to the Permian Yakuno paleo-island arc. The second-stage rocks are mainly arc granitoids that intrude … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Data sources for the mafic rocks in Yakuno ophiolite are excerpted from Suda and Hayasaka [7] and Ichiyama and Ishiwatari [11]. The metagabbros in Yakuno ophiolite plotted in this diagram were evaluated to be the melt origin which do not possess the cumulite compositions by Suda and Hayasaka [7].…”
Section: Geochemical Implications For the Evolution Of Babbmentioning
confidence: 99%
See 4 more Smart Citations
“…Data sources for the mafic rocks in Yakuno ophiolite are excerpted from Suda and Hayasaka [7] and Ichiyama and Ishiwatari [11]. The metagabbros in Yakuno ophiolite plotted in this diagram were evaluated to be the melt origin which do not possess the cumulite compositions by Suda and Hayasaka [7].…”
Section: Geochemical Implications For the Evolution Of Babbmentioning
confidence: 99%
“…Suda [8] and Suda and Hayasaka [7] suggested that the amphibolite and metagabbro in the Asago area possess geochemical affinities of BAB basalt (BABB), which are derived from a tholeiitic BABB source. These mafic rocks of BABB affinities are intruded by tonalite, quartz-diorite, and granodiorite of arc affinities.…”
Section: Yakuno Ophiolite and Associated Rocks In Asago Areamentioning
confidence: 99%
See 3 more Smart Citations